Acid‐Functionalised Magnetic Ionic Liquid [AcMIm]FeCl4 as Catalyst for Oxidative Hydroxylation of Arylboronic Acids and Regioselective Friedel–Crafts Acylation1. Issue 8 (17th July 2017) - Saha, Arijit; Payra, Soumen; Dutta, Dipa; Banerjee, Subhash
Abstract: An acid‐functionalised, magnetic, room‐temperature ionic liquid, 1‐acyl‐3‐methylimidazolium tetrachloroferrate ([AcMIm]FeCl4 ), was synthesised and its optical, magnetic, and thermal properties were investigated. The magnetic moment (0.05402 emu in 2 T magnetic fields) showed strong paramagnetic behaviour, and thermogravimetric analysis indicated very good thermal stability with a decomposition temperature higher than 230 °C. Additionally, [AcMIm]FeCl4 efficiently catalysed the oxidative ipso ‐hydroxylation of arylboronic acids and regioselective Friedel–Crafts acylation without external organic solvent or additives, such as acids, base, and ligands. This functionalised ionic liquid, [AcMIm]FeCl4, was recycled and reused at least six times without significant loss of its catalytic properties and stability. Abstract : Attractive separation : The facile oxidative hydroxylation of arylboronic acids and regioselective Friedel–Crafts (F–C; see scheme) acylation of phenols is demonstrated by using an acid‐functionalized magnetic ionic liquid (MAIL), 1‐acyl‐3‐methylimidazolium tetrachloroferrate ([AcMIm]FeCl4 ), as a catalyst and reaction medium.